Spontaneous enteroatmospheric fistula in a patient with COVID-19 disease - Yıldırım, Ali Cihat; Ekici, Mehmet Fatih; Zeren, Sezgin (Journal of Surgery and Medicine, 2022)
Coronavirus 2019 (COVID-19) disease patients present with upper respiratory symptoms; however, these patients may show gastrointestinal symptoms on arrival at the hospital. This finding requires an abdominal physical examination and imaging for 33% of patients. Enteroatmospheric fistulas (EAF) may form a connection between the external environment and the gastrointestinal tract and usually presents various difficulties in controlling the disease without surgical intervention. Its management requires a high level of clinical expertise to control and treat the fistula. In this case report, spontaneous EAF and its management are presented in a 65-year-old morbidly obese female patient who spontaneously had EAF during her hospitalization for COVID-19.